Partisipasi Masyarakat Dalam Pembentukan Peraturan Daerah di Kabupaten Kuantan Singingi - Ningsih, Zely Nanda; Hz, Evi Deliana; Junaidi, Junaidi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Community participation in the formation of Regional Regulations is a form of community involvement in forming regulations that will become the basis for legal certainty. In Kuantan Singingi, community participation has not been implemented optimally, there are many factors that are obstacles. In this thesis, the researcher will explain what are the obstacles so that it is hoped that suggestions will also be found so that community participation in the formation of Regional Regulations in Kuantan Singingi becomes more optimal. This research is a sociological legal research, this is based on field research which refers to interviews and observations statements as well supporting documents that have a corelation with the background of the problem to be studied. This study uses secondary date sources consisting of primary, secondary, and tertiary legal materials. This study uses qualitative date analysis by producing a deductive method of drawing conclusions, namely drawing conclusions from that are general to things that are specific. From the result of the discussion it can be concluded that the process in forming Regional Regulations in Kuantan Singingi has not been optimal in involving the community. This is due to the lack budget and the apathetic attitude of the community it self so that the Kuantan Singingi Regional Goverment in forming Regional Regulations prioritizes formal procedures.